2011
DOI: 10.1093/toxsci/kfr147
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exposure during the Third Trimester Equivalent of Human Gestation: Time Course of Effects on the Central Cholinergic System of Rats

Abstract: Up to 22% of pregnant women smoke, which constitutes a major health concern. Nicotine, a cholinergic agonist, causes deleterious effects on brain development. However, most studies investigate its effects during rodents' gestation, which corresponds, in terms of neural development, to the first two trimesters of human gestation. Here, we focused on effects of nicotine on the brain cholinergic system during the third trimester equivalent of human gestation. From the 2nd to the 19th day of lactation, dams were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…There is a biological basis for the associations between third trimester PCSE and offspring nicotine dependence. Laboratory research has found that in the third trimester of gestation, brain development is highly susceptible to nicotine (Nunes-Freitas et al, 2011; Slotkin, 2008; Lotfipour et al, 2010), and exposure during this time might be more likely to predict greater levels of problematic tobacco use. In a study by Slotkin (2008), there was an upregulation of nicotinic acetylcholine receptors (nAChR) among adult rats exposed to nicotine in the immediate neonatal period, a time comparable to the third trimester in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There is a biological basis for the associations between third trimester PCSE and offspring nicotine dependence. Laboratory research has found that in the third trimester of gestation, brain development is highly susceptible to nicotine (Nunes-Freitas et al, 2011; Slotkin, 2008; Lotfipour et al, 2010), and exposure during this time might be more likely to predict greater levels of problematic tobacco use. In a study by Slotkin (2008), there was an upregulation of nicotinic acetylcholine receptors (nAChR) among adult rats exposed to nicotine in the immediate neonatal period, a time comparable to the third trimester in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated nAChRs binding in left cerebral cortex, midbrain and hippocampus. The nAChRs binding method has been described in detail in previous papers (Abreu-Villaca et al, 2016;Lima et al, 2013;Nunes-Freitas et al, 2011;Ribeiro-Carvalho et al, 2008;Ribeiro-Carvalho et al, 2009). Briefly, tissues were thawed and homogenized (Ultra-Turrax T10 basic, IKA, São Paulo, SP) in 40 vols of ice-cold 50 mM Tris-HCl (pH 7.4), the homogenates were sedimented at 40,000 × g for 10 min and the supernatant solution was discarded.…”
Section: Nachrs Bindingmentioning
confidence: 99%
“…Aliquots were withdrawn for measurements of [3H]cytisine binding and for membrane protein evaluation (Bicinchoninic Acid kit). [3H]cytisine is a selective ligand that binds to the α4β2 nAChR, the predominant receptor subtype in the mammalian brain, and that is upregulated by nicotine (Abreu-Villaca et al, 2003;Nunes-Freitas et al, 2011;Ribeiro-Carvalho et al, 2008). Binding was determined using a final ligand concentration of 2 nM; specific binding was displaced with 100 μM nicotine.…”
Section: Nachrs Bindingmentioning
confidence: 99%
“…All assays have been described in detail in previous papers (Lima et al, 2013;Nunes-Freitas et al, 2011;Ribeiro-Carvalho et al, 2008) and will therefore be presented briefly. ChAT activity was assayed in tissue homogenate using 50 M [ 14 C]Acetylcoenzyme A.…”
Section: Aliquots Of This Resuspension Were Withdrawn For Measurementmentioning
confidence: 99%